Evaluation and modification of a micro irrigation technique - JACOB BIJO DANIEL; Prince George; Geethi Nath R; Er. Rema K. P (Guide) (Tavanur 1999 Kelappaji College of Agricultural Engineering and Technology)
Evaluation and modification of a micro irrigation technique
Evaluation and modification of a micro irrigation technique